The Ignorance of People to The Nature of God in Nawal El Saadawi's The Fall Of The Imam Novel (1987):a Sociological Approach - Putra, Dian Antana, Dr. Abdillah Nugroho. M.Hum, Drs. Sigit Haryanto. M.Hum (2016)
The major problem of this study is how the ignorance of people to the nature of God is reflected in The Fall of the Imam novel. The objective of this study is to analyze the novel based on its structural elements and on the sociological analysis. In analyzing The Fall of the Imam, the researcher uses sociological aspects. The data sources consist of primary data and secondary data sources. The primary data sourceis The Fall of the Imam novel and the secondary data sources are the other sources related to the analysis such as books of literary theory and the other relevant information. The method of the data collection is library research. The technique of data analysis is descriptive analysis. Based on the sociological analysis, in The Fall of the Imam, Nawal El Saadawi describes how the Imam in region that claims to be representative of God on earth. He oppresses and deceives people in the name of God. The Fall of the Imam is a true novel condition in situation social-religion culture in Egypt. Sociological perspective is essentially the scientific, objective of the study of people in society, the study of social institutions and social processes.